Adolescentes em conflito com a lei: transgressões, estigmas e representações sociais - BASTOS, Suellen Gardênia Santos (2015)
This study summarizes the understanding of social representations involving teenagers, considered in conflict with the law. It was made by the perspective of legal, health care and family speeches by representatives of the 2nd Prosecutor of Children and Youth of St. Louis, the Association of Mothers and Friends of Children and Adolescents at Risk (AMAR), the Foundation for Children and Adolescents of Maranhao (FUNAC), and the self-representation of teenagers. The theoretical and methodological approach that supports the analysis was based on theories of social representations and sociological perspectives that addresses issues such as transgressions, deviations and stigmas, commonly attributed to these teenagers. The empirical research consisted of interviews with those involved in this set of speeches, technical reports and gathering information in files of the 2nd Prosecutor for Children and Youth of St. Louis, relating to its activities in the years 2007-2009.